THE IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS AND EFFECTIVENESS OF FINANCIAL MANAGEMENT OF HAJJ FUNDS ON THE QUALITY OF HAJJ FINANCIAL REPORTS AT BPKH BEKASI CITY (PERIOD 2020 – 2022) - Rahmat Yuliansyah; Said Khaerul Wasif; Desi Amaliati; Farmansjah Maliki (Bajang Institute, 2024)
This research aims to test the application of government accounting standards and the effectiveness of Hajj fund management on the quality of Hajj financial reports at BPKH Bekasi City for the 2020 - 2022 period. This study uses a quantitative approach. The research population used Hajj and Umrah (PHU) employees at BPKH Bekasi city. Sampling in this study used purposive sampling, namely taking samples from a population of 31 respondents. The analytical method used is multiple linear regression test analysis. The data processing tool is SPSS 26. Based on this research, it shows that: 1). Partially, the variable role of government accounting standards has a significant effect on the quality variable of Hajj financial reports 2). The variable effectiveness of Hajj fund management has a significant effect on the quality of Hajj financial reports at BPKH Bekasi City. Originality/Value this article with the title Implementation of Government Accounting Standards and Effectiveness of Financial Management of Hajj Funds on the Quality of Hajj Financial Reports at BPKH Bekasi City (Period 2020 – 2022). The artikel is original and is not an imitation, duplication or plagiarism of scientific work that has been published and/or has been used for publication in other articles or journals except for the part where the source of the information is properly stated. If in the future it can be proven that there are elements of imitation, duplication or plagiarism, then I am willing to accept sanctions in accordance with applicable laws and regulations